Plasma Very Low Density Lipoprotein and Fat Deposition in Commercial Broiler and Crossbred Village Chickens - Tan, Bee Koon (2002)
A study was conducted to determine the relationships between triacylglycerol (TAG) of plasma, very low density lipoprotein (VLDL), VLDL subfractions; postheparin plasma lipoprotein lipase (LPL) activity and fat deposition in two different breeds of chickens. The VLDL apolipoproteins of both breeds were also characterised. Two breeds used were crossbred village chicken (AK) (Sasso crossed) and commercial broiler (CB) (Avian). One hundred and eighty day-old female and 180 day-old male birds from both breeds were used in this study. They were fed a conventional starter diet up to three weeks of age and a finisher diet until six weeks of age for CB and 12 weeks of age for AK. They were housed in six pens with 30 female and 30 male birds of each breed per pen. Three male and three female birds from each pen were slaughtered and the blood was collected. The VLDL was isolated and sub fractionated by using Fast Protein Liquid Chromatography (FPLC). Lipid compositions and types of apolipoproteins were determined. The LPL activity in the postheparin plasma was also measured by using non-esterified fatty acid kit. The body weight (BW) and feed intake (FI) of CB were significantly (P<0.01) higher than that o f AK but the feed conversion ratio was significantly (P<0.01) lower. Fat deposition of both breeds was positively correlated (P<0.01) with BW and FI. Fast Protein Liquid Chromatography analysis showed the presence of two sub fractions in VLDL. Subfraction 2 contained more apo E than sub fraction 1 and believed to enhance the lipolysis process of VLDL TAG. The results also showed that CB had a significantly higher proportion of sub fraction 2 (P<0.01), bigger VLDL particle size (P<0.01) and higher postheparin plasma LPL activity (P<0.05) than AK. All these factors lead to a higher fat deposition in CB (P<0.01) than that of AK. These results were further supported by the lower VLDL TAG concentration of CB (P<0.01). The CB, which had a higher LPL activity and proportion of sub fraction 2, caused a faster catabolism of TAG and more fatty acids were released for fat deposition. The AK and CB have almost similar types of apolipoproteins in both sub fractions I and 2. The AK showed the presence of apo AI, AIV, D and E whereas the CB had apo AIV, D, E and H. The apo AIV and apo E were present in both sub fractions of AK and CB.